(3NRGfI GdSdGMs
(3ChdgG (B:s
(3hHYO(B: (3agPg QSGdI cJHJgG Ydi hab GdCbJQGM, hSejJgG NRGfI GdSdGM, JWYf UOhQ GdeYGfOjf HQeGM CdaJgG hJQej ebGJd GdCZQGV HbSi fhfGJgG hJJMUf ef SgGe GdbOM HLff dGeGJgG s
(3BNQgG (B:s
(3hjQhj eOGgG Ydi Whd eOGgG ef Oe ef HZi Ch caQ hjLYd CHhGHgG GdTQjaI CYPH efgd jQOg GdHYjO hGdbQjH, hCefY MQe jdLC Edjg GdCgjd hGdZQjH Hefg hjefg s
(3hgj QSGdI JTJed Ydi oeNJGQGJ fKQjI hTYQjI aj hUa GdSdGM CdaJ ddSdWGf CHj GdaJM CMeO TGg Hf eMeO TGg Hf eXaQ TGgs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B283 s
Keywords: (3GdCOHs